Comparative study on the use of different isibox system. - Esquivel, Dante (College of Fisheries, University of the Philippines, 1982)
Two sets of isbox system were constructed. Five plastic crates were utilized for one set and five banyeras for the other. Melting rate of crushed ice in these two systems and in the control (five piled banyeras each covered with sack) were monitored every two hours for twenty-four hours. Then actual use of the system was carried out on-board R/V sardinella. Fifteen kilograms of slip mouth (leiognathus bindus) were packed in each container, and the chilling temperatures were monitored, using thermocouples, up to ten hours.